Theological foundations for an effective Christian response to the global disease burden in resource-constrained regions - Daniel W. O'Neill (Health for All Nations, 2016)
Given the global disease burden and resource disparity that exists in the world and the globalization of Christianity, Christians are in a critical position to effect radical change in individuals, communities and systems for human flourishing. This paper describes the theological basis of seven key elements that the Church can contribute to sustainable development, global health equity, and universal access as an expanding movement: defining health, speaking truth, providing care, making peace, cooperating, setting priorities, and mobilizing resources for maximum stewardship in low resource settings.